Penerapan manajemen risiko pada usaha mikro kecil dan menengah: Kajian literatur terhadap keberlanjutan usaha - Ambiya, Ahmad Zhafa (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the implementation of risk management in Micro, Small, and Medium Enterprises (MSMEs) and its impact on business sustainability. The method used is a literature review by analyzing various academic sources such as journals, books, and relevant scientific publications. The results show that risk management plays a crucial role in helping MSMEs identify, analyze, and control various types of risks, including operational, financial, and market risks. The proper implementation of risk management can enhance business resilience, minimize potential losses, and support long-term sustainability. However, the implementation of risk management in MSMEs still faces several challenges, such as limited resources, lack of knowledge, and low awareness of the importance of risk management practices. Therefore, efforts are needed to improve literacy and provide support from various stakeholders to ensure that risk management in MSMEs can be implemented effectively and sustainably.